Money in Islam: Toward Re-evaluation of Islamic Financial System - Khoriul Umam (Falah: Jurnal Ekonomi Syariah, 2017)
This paper aims at re-evaluating the Islamic financial system based on its authenticity in the perspective of money in Islam. Imam Ghazali identifies two main functions of money: as a just unit of account and an efficient medium of exchange. These two functions are the purpose of money creation. Thus, Islam prohibits any activity diverting money from carrying out its functions. On the basis of this perspective, the current practice of Islamic banking thatcreates dominantly debts from sales and leasebased products and not the profit and loss sharing ones has caused money deviated from its functions. Furthermore, in Islamic capital market, this paper insists that the minimum holding period of Islamic stock market cannot abolish the practice of capital gain in the secondary market of Islamic capital market. Accordingly, Keynesian liquidity preference must exist as well as the speculative motive of money demand. As the result, money will be demanded not only for real economic activities, so the supply of money will overshoot the demand of real economic activities. Such condition distorts the ability of money to provide a true value for real economic activities. On the basis of these points of view, innovations in Islamic financial system should be designed to facilitate money providing a just value of economic activities and facilitating exchange of goods and services in efficient and equitable manner. Finally, this paper sees the need of Ulama who can control the innovation in Islamic financial system to be based on its authenticity that finally leads to the achievement of Islamic vision. In this regard, faculty should design its curriculum that provide graduates who are able to remove the western vision from Islamic finance theories and then to infuse the Islamic vision to them.